A Single Stage Dilute Nitric Add/Salt Oxidation and Leach Process - Angus W. Morrison; Lee F. Robinson; Norman M. Anderson (Society for Mining, Metallurgy & Exploration, 1990)
About 100 years ago the acid and chlorine oxidation routes for gold extraction were abandoned in favour of cyanide/ oxidation processes. Now a return to acid processing is in progress. One publication in particular led HM C Technology to investigate the reaction of dilute nitric acid and alkaline metal chlorides with refractory gold ores.(l) The one stage system of gold and silver recovery from sulphidic ores is described below. It is rapid and does not use large or expensive plant or special pressure equipment. It eliminates calcining followed by cyanidisation and shows a simple way of recovering the gold directly. Patents have been granted in some countries (2).